Malignant Tumor of Peripheral Nerve Sheath in the Thoracolumbar Region in a Cat - Vieira Amorim Da Costa, Fernanda; Grünwalder Paim , Mirela; Basseggio Rivas, Bárbara; Froner Argenta, Fernando; Sonne, Luciana (Acta Scientiae Veterinariae, 2023)
Background: In veterinary medicine, peripheral nerve tumors (PNST) are classified from the cellular pattern and as benign and malignant (MPNST). The majorities of cases are benign and usually involve the skin and subcutaneous tissue of the head, neck, and limbs. Animals with MPTNS usually have spinal cord and spinal canal involvement and are also described in the small and large intestine, oral cavity, perirenal region, and urinary bladder. Treatment is performed according to the location of the neoplasm and metastasis is rarely described. The present article aims to report a case of a malignant tumor in the peripheral nerve sheath of a cat. Case: A 8-year-old domestic cat was presented with a history of progressive paresis in the pelvic limbs. On neurological evaluation, proprioceptive ataxia and proprioception deficit in the pelvic limbs were observed, suggestive of thoracolumbar injury. Blood work and serum biochemistry showed results within the reference for the species and the bi-directional immunochromatography test for FIV and FeLV were negative. The radiographs of the thoracolumbar segment did not show significant changes. Myelography with iodinated contrast and collection of cerebrospinal fluid (CSF) were performed. On myelography examination, iodinated contrast loss was found between the 6th and 7th thoracic vertebrae, while the CSF analysis was normal. The patient underwent laminectomy and durotomy for excision of a mass found dorsally to the spinal cord, with intradural location. The tumor was sent for histopathological examination. Microscopic analysis showed neoplastic proliferation of spindle-shaped cells with predominance of the Antoni A pattern. Immunohistochemical analysis demonstrated intense cytoplasmic staining of the neoplastic cells for vimentin and S100 protein. Based on these findings, the diagnosis of malignant peripheral nerve sheath tumor was made. Radiotherapy was suggested as adjuvant treatment after surgical procedure. However, the owner refuse to follow this recommendation due to cost restriction. The patient had a satisfactory clinical recovery, he has no longer presented proprioceptive ataxia or proprioception deficits in three months after the surgical procedure. Discussion: In the case described, the feline patient presented a history, clinical signs, and findings in the myelography exam related to MPNST in the region of the vertebral canal. This neoplasm usually involves the spinal canal or spinal cord, but has been described in other locations, such in the small and large intestine, oral cavity, perirenal region, and urinary bladder. Based on the findings of the physical examination and complementary exams, a surgical procedure was recommended. Then, laminectomy and dutoromy were performed to remove the mass. The treatment described in the literature in cases of MPTNS is surgery, which can be curative, but in some cases, the use of radiotherapy may be necessary. The histological patterns observed in this neoplasm are the Antoni A and B, in the case described the Antoni A pattern was observed. The definitive diagnosis was made by immunohistochemistry with vimentin and S100 protein. MPNST are few described in the thoracolumbar region in cats. The surgical treatment was curative, where improvement of the clinical signs could be observed three months after surgery. In addition, monitoring of patients is recommended to ascertain relapses and metastases. Keywords: feline, neurosurgery, histopathology, immunohistochemistry.